The Micro‐Broadband Receiver (μBBR) on the Very‐Low‐Frequency Propagation Mapper CubeSat. Issue 11 (8th November 2021) - Marshall, Robert A.; Sousa, Austin; Reid, Riley; Wilson, Gordon; Starks, Michael; Ramos, Daniel; Ballenthin, John; Quigley, Steven; Kay, Ron; Patton, James; Coombs, Joseph; Fennelly, Judy; et al.
Abstract: The very low frequency (VLF) propagation mapper (VPM) is a 6U CubeSat designed to measure VLF radio waves in Low‐Earth Orbit. The science goals of the VPM mission are to measure VLF signals broadcast by the DSX mission, and to study natural and anthropogenic signals (from lightning and VLF transmitters) in the near‐Earth space environment. The primary payload consists of an electric field dipole antenna deployed to 2 meters in length, and a magnetic search coil deployed 50 cm from the spacecraft. Signals from these two sensors are conditioned by analog electronics, sampled, and then processed digitally into downloadable data products. The VPM mission was launched in January 2020; science operations began in March 2020 and continued through September, when contact with the spacecraft was lost. This paper describes the mission goals and instrument designs in detail, as well as some examples of the VPM data set. Plain Language Summary: The very low frequency (VLF) propagation mapper (VPM) is a 6U CubeSat designed to study radio signals from lightning, ground‐based transmitters, and space‐based transmitters and how these signals propagate through the Earth's ionosphere and magnetosphere. This paper describes the mission goals and instrument design; the instrument onboard VPM includes an electric field sensor and a magnetic field sensor. Preliminary data is presented to give a first taste of the VPM data set. The VPM mission was launched in January 2020; science operations began in March 2020 and continued through September, when contact with the spacecraft was lost. Key Points: The very low frequency (VLF) propagation mapper (VPM) CubeSat was designed to measure VLF waves from low Earth orbit We present the VPM instrumentation suite, consisting of an electric field dipole antenna, a magnetic search coil, and a data processing unit We present example data from the VPM flight mission, demonstrating the capability of the μBBR receiver